Water solutions for inclusive growth: IWMI’s Gender Equality and Social Inclusion (GESI) Portfolio - International Water Management Institute (International Water Management Institute, 2025)
This document provides a comprehensive overview of the International Water Management Institute's (IWMI) Gender Equality and Social Inclusion (GESI) portfolio. It underscores IWMI's dedication to incorporating gender equality and social inclusion into its research and development efforts, with a focus on scalable solutions that foster economic empowerment and leadership opportunities for underrepresented groups. The brochure details significant GESI research and projects aligned with IWMI's three strategic focus areas: mitigating water risks, addressing global inequalities, and promoting sustainable water management. Additionally, it outlines future research directions for the IWMI GESI portfolio, including the use of intersectional data for smarter decision-making, empowering youth as leaders in the water sector, responsibly scaling water innovations, integrating indigenous knowledge for water security, and shaping policy pathways for gender-equitable water governance. The document highlights the importance of partnerships and funding from leading global donors to drive long-term, systemic change in water management and achieve a water-secure world for all.